Analisis Implementasi Desain Pembelajaran pada Proses Pembelajaran di SDN Cikokol 1 Kota Tangerang - Magdalena, Ina; Sulaiman, Abdul Mugni Saudi; Sukma, Frizori Rendy (Lembaga Yasin AlSys, 2023)
The purpose of this research is to analyze the learning process in the classroom in elementary schools. in this study using a qualitative descriptive method. In a learning process where an educator must be required to produce superior and competent generations in all fields. This is really not easy to do by an educator who has absolutely no ideas and strategies in delivering learning material. In learning the teacher's most important task is to condition the environment to support changes in behavior for students. formulation of strategies that can be implemented to achieve goals including methods, techniques and media that can be utilized as well as evaluation techniques to measure or determine success. The objectives in this study are as follows to describe the implementation of learning designs in an effort to increase motivation and describe the implementation of learning designs in an to improve student achievement. there is an analysis which is the decomposition of a subject into its various parts and the study of the parts themselves and the relationships between the parts to obtain a proper understanding and understanding of the meaning of the whole.